Passiflora nebulosae (Passifloraceae, subgenus Tryphostemmatoides) a distinctive new critically endangered species discovered in the Colombian Andes - Restrepo, Jorge Julián; Ocampo, John; Giraldo, Wilmer (Magnolia Press, 2019)
A new species of Passiflora belonging to the subg. Tryphostemmatoides from Colombia in the Andean region is described and illustrated from living material, as well as from herbarium specimens. Passiflora nebulosae Restrepo & Ocampo is similar to P. discophora and P. pacifica, but can be recognized mainly by its petiole length (up to 8 mm), leaf margin glands (6‒10), coriaceous leaves, peduncle bifurcate, operculum margin crenate, and limen margin lacerate. The new species is a narrow endemic discovered in cloud forest margins between 1750‒2352 m. It is regarded as critically endangered (CR) because of its restricted occurrence with a small population size.